Size, Sunk Cost and Judge Bowker's Objection to Free Trade - McLaren, John (American Economic Review, 1994)
This paper studies trade liberation between a lag country and a small one. We make two key assumptions, suggested by political debates on trade reform in small countries. First, future production requires an irreversible investment now. Second, There is a the possibility of future trade negotiations. Strikingly, anticipated trade negotiations mau make the small country strictly worse off than a fully anticipated trade war, and indeed worse off than autarchy. The reason is a negative strategic externality in the small country conferred by anyone investing in country into trade with the large one, harming its bargaining trade, so that anticipated bargeing benefits the small country on balance only if (i) the two economies are sufficiently different, and (ii) there are sufficient substitutions possibilities in consumption.